Phase Transitions of Simple Systems - Smirnov, Boris Mikhaĭlovich (Springer, 2017)
This monograph develops a unified microscopic basis for phases and phase changes of bulk matter and small systems in terms of classical physics. The origins of such phase changes are derived from simple but physically relevant models of how transitions between rigid crystalline, glassy and fluid states occur, how phase equilibria arise, and how bulk properties evolve from those of small systems.